Analysis of Drug Repositioning and Prediction Techniques: A Concise Review - He, Shida; Liu, Xin; Ye, Xiucai; Tetsuya, Sakurai (Current Topics in Medicinal Chemistry, 2022)
High costs and risks are common issues in traditional drug research and development. Usually, it takes a long time to research and develop a drug, the effects of which are limited to relatively few targets. At present, studies are aiming to identify unknown new uses for existing drugs. Drug repositioning enables drugs to be quickly launched into clinical practice at a low cost because they have undergone clinical safety testing during the development process, which can greatly reduce costs and the risks of failed development. In addition to existing drugs with known indications, drugs that were shelved because of clinical trial failure can also be options for repositioning. In fact, many widely used drugs are identified via drug repositioning at present. This article reviews some popular research areas in the field of drug repositioning and briefly introduces the advantages and disadvantages of these methods, aiming to provide useful insights into future development in this field.
Keywords: Drug redistribution